A new wave of solidarity in a sea of economic interests - Aranguiz, Ane (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2020)
A decade after the game-changing cases of Viking and Laval where the European Court of Justice (ECJ) decided in favour of the freedom to provide services and establishment over the right to collective action, the Commission launched the European Pillar of Social Rights (EPSR), which could be key in reversing the damages that these cases caused to social protection in the EU. Viking and Laval symbolised the imbalances between the (mostly) national social systems and the EU-wide internal market. These cases and the following jurisprudence added to the relative weakness of the EU's social dimension - which is seen as insufficient to counterbalance the hollowing out of the national social systems-proved the necessity of bringing "the social" to the core of the EU, giving sense to the objective set in Article 3 TEU of the EU being a social market economy. A true social market economy is compelled to address the issue of asymmetry between the "social" and the "market" that is so inherent to the EU, which requires, at the very least, to put in place a coordinated approach to social protection between the Member States. The EPSR represents a renewed consensus that social progress is central to the European project. This article discusses the possibilities that the EPSR offers to redress the imbalances in EU law by challenging the primacy given to the internal market over other EU policies. The role of the EPSR is discussed from the perspective of the latent impact of this instrument in contributing to the policy objective of fighting poverty and social exclusion.